The presence of lice species on wild geese in the Elazig district - Aksin, N (Scientific Technical Research Council Turkey, 2004)
The purpose of this study was to determine the presence of lice species on wild geese in the Elazig district. Twenty wild geese were inspected for lice species between January and February in 1998 and 2001. Nine of these geese had been exposed to lice infestations and Anaticola anseris (Linnaeus, 1758) composed all the collected 92 lice. The morphological description of A. anseris was based on microscopy and microphotography pictures were taken.
Keywords: lice; Anaticola anseris; goose